GABBY: An ex vivo model for learning and refining the technique of preformed silo application in the management of gastroschisis - Dabbas Natalie; Muktar Zahid; Ade-Ajayi Niyi (Wolters Kluwer Medknow Publications, 2009)
Background: Gastroschisis (GS) is a congenital full-thickness defect of the anterior abdominal wall, whose incidence is increasing. Traditional postnatal management options include primary reduction and closure under general anaesthetic or operative silo construction for defects judged to be unsuitable for immediate repair. The cot-side application of the preformed silo (PFS) with delayed abdominal wall closure has recently been advocated as the management method of choice for infants with GS. We report a novel trainer designed to facilitate acquisition and refinement of the skills to apply the PFS. Materials and Methods: A model of an infant with GS was constructed to allow application of a PFS. Each step of the clinical application of a PFS could be simulated. Paediatric surgeons at a regional meeting participated in evaluating the model. This cohort was surveyed with regards to previous clinical experience applying the PFS, invited to apply the silo on the model and then resurveyed with regard to the technique, ease of the application of the PFS on the model, its robustness and potential use as a training tool. Results: Seventeen paediatric surgeons completed the surveys and applications of the PFS on the model. Under supervision, each step of the procedure was completed by all participants. Feedback was enthusiastic and positive and participants judged the model to be realistic and potentially very useful as a training tool (median score 8 out of 10). Conclusions: We have developed and evaluated a reproducible, low-cost model of an infant with GS. This ex vivo trainer may be a useful adjunct in the acquisition and refinement of the skills of surgeons who manage GS using a PFS.